Dynamic performance analysis of a noncircular cylindrical floating ring bearing. (June 2017) - Soni, Sandeep; Vakharia, DP
The performance of a noncircular cylindrical floating ring bearing under the laminar flow condition has been analyzed. The noncircular cylindrical floating ring bearing is a modified version of the plain cylindrical floating ring bearing in which the outer bearing of the cylindrical floating ring bearing is changed in the form of lobed pattern. The noncircular patterns are known for its better stability and stiffness behavior according to the magnitude of applied loads. The finite element analysis has been used to solve the classical Navier–Stokes equations in the cylindrical coordinates of the modified form along with the continuity equation that represents the fluid flow field in the clearance space of the noncircular cylindrical floating ring bearing. The numerical data are for a proposed bearing with the length to diameter ratio of 1.0, and values of the ratio of film clearances of 0.70 and 1.30. Performance characteristics of a finite noncircular cylindrical floating ring bearing has been studied in terms of the inner and outer film eccentricity ratio, Sommerfeld number, attitude angle, stiffness and damping coefficients, equivalent support stiffness coefficient, whirl frequency ratio, and critical journal mass at various values of the outer film eccentricity ratios. The proposed analysis disseminates that the dynamic performance parameters of the noncircular cylindrical floating ring bearing are much better than the plain cylindrical floating ring bearing.